Journal of Applied Informatics and Technology (Full Issue): Vol. 4 No. 1 (2022): January-June - Journal of Applied Informatics and Technology (Journal of Applied Informatics and Technology, 2022)
Contents - Comparison of NDWI, MNDWI1 and MNDWI2 Indices from Sentinel-2 Satellite Images for Extracting Urban Surface Water Bodies in Khon Kaen (p. 1-12) - A Comparative Sustainable Assessment between Native Durian-Based Agroforestry System and Commercial Durian-Based Mixed Orchard in the Upstream of Ban Dan Na Kham Sub-district, Uttaradit Province (p. 13-31) - Positional Accuracy Evaluation of Google Earth using RTK GNSS Network Surveying Case Study: Mahasarakham Province (p. 32-47) - Development of Smart Circuit Breakers to Prevent Fire from Short Circuit Current (p. 48-61) - Developing the Warehouse Management Online System (p. 62-70) - Analysis of Lime Leaf Disease using Deep Learning (p. 71-86)